Evaluation of the Development Level of Low-Carbon Tourism in Chinese Cities - Mao, Shuai; Li, Haihong; Cai, Xiang; Liu, Fengqin; Zhong, Hong; Song, Yang (Frontiers in Environmental Science, 2022)
Low-carbon tourism reflects the degree of environmental concern in the tourism industry, and is also the foundation of green, sustainable and ecological tourism. The transformation of tourism industry, known as the sunrise industry, to low-carbon pattern contributes to the sustainable development of tourism cities. In this paper, an objective evaluation indicator system for low-carbon tourism cities is constructed from the three dimensions of economy, environment, and society, followed by the determination of the weights of the evaluation indicators using analytic network process (ANP) model. Ten low-carbon pilot cities in China are evaluated using the statistics data of the two years of 2014 and 2019. The main research results show that when a city’s economy has reached a certain level, with the economy and people’s income further developing and the environmental pollution being gradually weakened, the city’s development level of low-carbon tourism will also be better. Besides, although these ten low-carbon pilot cities have similar development level in terms of society dimension, they have great differences in the economy and environment dimensions. The tourism cities with better economic development levels also rank higher in low-carbon environment and ecological environment, and the overall development level of low-carbon tourism is also better, which shows obvious Matthew effect as a whole. This paper provides targeted policy recommendations for the construction of low-carbon tourism cities in China.